Pengaruh Orientasi Kewirausahaan Terhadap Kinerja UMKM Di Kota Waingapu - Marlon Hamba Pulu; Betseba Haba; Jendriantika Ndamung; Alfian Balla K. Marak; Tumpal Pangihutang Situmorang (Politeknik Ganesha Medan, 2025)
The purpose of this study was to examine the influence of dimensions of innovativeness, risk taking, and proactiveness on the performance of Micro, Small and Medium Enterprises (MSMEs) in Waingapu City, both partially and simultaneously. The population of this study was culinary MSMEs around Waingapu City District, East Sumba Regency, which were chosen because of the rapid growth of MSMEs in that location. The sampling technique used was purposive sampling, with the criteria that MSMEs had been running a business for one year. Based on hypothesis testing using multiple regression, the results of the study showed that simultaneously and partially, entrepreneurial orientation variables consisting of proactiveness (X1), innovativeness (X2), and risk taking (X3) had a significant effect on MSME performance. These results indicate that proactiveness, innovation, and courage to take risks have a positive and significant impact on MSME performance.